Respons Investor Sebelum dan Sesudah Penerbitan Sukuk - Su'ud Wahedi; Zainol Hasan; Musyaffa Rafiqie (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2022)
This research aims to analyze the difference of investors' reaction between before and after the announcement of sukuk or syariah bond by some enterprises which listed in Indonesian Stock Exchange. Based on the observation, there are 34 enterprises which announce sukuk emission, but only 14 enterprises which are decided to become samples in this research. Data of stock price is collected from website of Indonesian Stock Exchange then analyzed by paired sample t-test technique. The result indicates that there is no difference of investors' respond between before and after issuing sukuk. Based on the result, it can be understood that investors do not consider the sukuk emission as crucial issue, so they do not take decision to buy or sell shares in hurry that cause abnormal gain or loss. Suggestion for next research is to expand samples in order to get more robust result.